2015
DOI: 10.5539/ass.v11n9p326
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Patient to Nurse Ratio on Quality of Care and Patient Safety in the Medical and Surgical Wards in Malaysian Private Hospitals: A Cross-sectional Study

Abstract: Background and objective: Nursing shortage and inadequate hospital nursing jeopardized quality of care and patient safety. This study aims to predict the impact of patient to nurse ratio on quality of care and patient safety in medical and surgical wards in Malaysian private hospitals. Methods:Cross-sectional data collected by questionnaire from 652 nurses working in the medical and surgical wards in 12 private hospitals participated in the study. Stratified simple random sampling performed to invite small siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…To meet the retention rate, the organization must strive in their efforts of QWL operations. Building and sustaining a healthy and balanced work life for nurses in the private hospitals is imperative for enhancing job satisfaction, improving performance and productivity in aspects of quality of patient care and safety and reducing turnover (Jarrar et al, 2015;AlMalki, 2012). This will, in turn, improve organizational performance and productivity (Mebarki et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To meet the retention rate, the organization must strive in their efforts of QWL operations. Building and sustaining a healthy and balanced work life for nurses in the private hospitals is imperative for enhancing job satisfaction, improving performance and productivity in aspects of quality of patient care and safety and reducing turnover (Jarrar et al, 2015;AlMalki, 2012). This will, in turn, improve organizational performance and productivity (Mebarki et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…15 These inconsistent findings in the previous studies make investigation of the impact of an intervening factor of hospital nurse staffing on the QC and PS essential for a better understanding of these relationships. 23 Therefore, the study investigates patient-centeredness as an intervening factor affecting these relationships because patient care is the focal point of care.…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, there are less than 10 institutions (public and private) awarding a degree in the medical field ( Khoo & Richard, 2002 ). Thus, medical and nursing workforce is still deficient ( Jarrar, Abdul Rahman, & Shamsudin, 2015 ), with a low proportion of bachelor’s degree holders ( Abdul Rahman, Jarrar, & Don, 2015 ; Khoo & Richard, 2002 ). A current study in the Malaysian hospitals found that less than 10.0% of nurses are holding a bachelor’s degree, and over 90.0% are holding a diploma ( Coomarasamy, Wint, & Sukumaran, 2015 ; Yaakup, Eng, & Shah, 2014 ).…”
Section: Resultsmentioning
confidence: 99%